The bile acid taurocholate impairs rat cardiomyocyte function: a proposed mechanism for intra-uterine fetal death in obstetric cholestasis - WILLIAMSON,C; GORELIK,J; EATON,BM; LAB,M; SWIET,MD; KORCHEV,Y (Clinical Science, 2001)
Obstetric cholestasis is a liver disease of pregnancy that can be complicated by sudden, hitherto unexplained, intra-uterine fetal death. Because intra-uterine death occurs suddenly, and because fetal heart rate abnormalities have been reported in obstetric cholestasis, we hypothesized that intra-uterine death is caused by impaired fetal cardiomyocyte function, resulting in fetal cardiac arrest. Obstetric cholestasis is associated with raised levels of maternal and fetal serum bile acids, and we propose that these may alter cardiomyocyte function. It was not possible to investigate the effects of bile acids on the intact human fetal heart at a cellular level. Therefore we used the closest available model of fetal myocardium at term: a primary culture of neonatal rat cardiomyocytes in which cells beat synchronously and develop pacemaker activity. The effect of the primary bile acid taurocholate (0.3 mM and 3 mM) on cultures of single cardiomyocytes, each with its own independent rate of contraction, was a reversible decrease in the rate of contraction and in the proportion of beating cells (P < 0.001). Addition of taurocholate to a network of synchronously beating cells caused a similar decrease in the rate of contraction. Furthermore, the integrity of the network was destroyed, and cells ceased to beat synchronously. Taurocholate also resulted in altered calcium dynamics and loss of synchronous beating. These data suggest that raised levels of the bile acid taurocholate in the fetal serum in obstetric cholestasis may result in the development of a fetal dysrhythmia and in sudden intra-uterine death.